Uji Disolusi Terbanding Tablet Lisinopril 10 mg - Yuti Mutiawati; Taofik Rusdiana; Mutakin Mutakin; Fitrileni Fitrileni (Fakultas Farmasi Universitas Setia Budi, 2014)
Lisinopril is an oral angiotensin converting enzyme (ACE) long acting, based on the characteristics of biopharmaceutics, lisinopril has a high solubility, but low permeability, this causes limitations in bioavaibility. The composition of lisinopril tablets wre calcium hydrogen phosphat anhydrous and mannitol as a filler, poly vinyl pyrrolidone K 30 as binder, cros carmellose sodium as a desintegrator, edicol rasbery red as a collor, Vitamin E TPGS NF (d-tocopheryl polyethylene glycol 1000 succinate) as enhancers of absorption / permeability with various concentrations, silicon dioxide colloidal, talc and magnesium stearate as glidant and antiadherent, aquadest and alcohol 95% as wetting agent. The study used wet granulation method. Test was done for the granule and tablet tested, including the comparative dissolution test with the innovator product. The result showed that the granule and the tablet were met the requirements. Vitamin E TPGS 1000 NF wasn’t affect to the comparative dissolution test result between the tablet product and the innovator product.